Malay Language Consonants Contact Pattern Based On Electropalatography Epg3 And Flex Epg System - Zin, Syatirah Mat (2019)
Electropalatography (EPG) is a medical instrument used in detecting contact pattern between the tongue and hard palate during a continuous speech. EPG contact pattern was built as a guideline for speech study and can be used to guide speech therapist during a treatment. In this study, the EPG3 system is used as an instrument for developing the Malay language consonants contact pattern. Thirty (30) Malay subjects without speech or hearing difficulties were selected in this study. All subjects were required to wear Reading palate and produce 15 Malay consonants in this study. The results indicate in the production of bilabial, velar and glottal cosonants, more contacts were located at the posterior of the hard palate. Meanwhile, in the production of alveolar and postalveolar consonants, the contact pattern were more on the anterior part of the hard palate. Besides, the design and development of new EPG system, namely Flex EPG system was also included in this study. The new EPG system features a Bluetooth technology, which overcomes the major lack of the EPG3 system. The development architecture of the Flex EPG system can be classified into two parts which are the Flex EPG hardware components and the Flex EPG software configuration. Additionally, the Flex EPG hardware consists of the Flex EPG palate and the electronic circuit. For the data collection, the Flex EPG palate was used to detect the tongue and hard palate contact by identifying the electrodes signal. The patterns of the contact are transmitted to a computer for display, storage, and analysis via a Bluetooth module.